A multicentre randomised controlled trial of Transfusion Indication Threshold Reduction on transfusion rates, morbidity and health-care resource use following cardiac surgery (TITRe2). - Reeves, B; Pike, K; Rogers, C; Brierley, R; Stokes, E; Wordsworth, S; Nash, R; Miles, A; Mumford, A; Cohen, A; Angelini, G; Murphy, G (NIHR Health Technology Assessment Programme, 2016)
The study found that a restrictive transfusion threshold of red blood cells is not superior to a liberal threshold after cardiac surgery. This finding supports restrictive transfusion due to reduced consumption and costs of red blood cells. However, secondary findings create uncertainty about recommending restrictive transfusion and prompt a new hypothesis that liberal transfusion may be superior after cardiac surgery.